Громадянське суспільство і громадянин у сучасному демократичному суспільстві - Горішня, К. О. (ХНУРЕ, 2025)
The article considers the problems of formation and development of the concept of citizenship in modern digital society. It is proved that. the formation and formation of a citizen is an important state task that can be solved within various areas of information, educational and cultural policy. In the modern domestic practice of political socialization and civic education, there are many unresolved problems. Researchers believe that overcoming these problems should begin with eliminating the conceptual contradiction between what is and what should be: defining certain characteristics of a citizen that are needed by the modern Ukrainian state.
Keywords: демократичне суспільство; громадянське суспільство